Pengaruh Baby Blues pada Interaksi Ibu dan Kesejahteraan Emosional Anak - Koenarso, Dyah Ageng Pramesty; Fajarwati, Ayu; Sari, Annisa Herlida (Muadalah, 2024)
This article explores the impact of Baby blues on the emotional well-being of young children, focusing on how this condition affects emotional attachment and the quality of interaction between mother and child. Baby blues is a common condition experienced by mothers postpartum and can negatively influence family dynamics, particularly in child-rearing. This study occupies a significant position in the discourse of child developmental psychology by highlighting the often-overlooked emotional impact of Baby blues on children. Using a qualitative method with in-depth interviews of ten mothers who experienced Baby blues, this research employs attachment theory to analyze the collected data. The findings reveal that children of mothers with Baby blues tend to experience emotional issues such as anxiety, insecurity, and stress, which correlate with decreased interaction quality and emotional distance between mother and child. The conclusion of this study underscores the importance of early intervention and strong social support for mothers experiencing Baby blues, as well as the development of holistic strategies to minimize the negative impact on the emotional well-being of children. These findings contribute significantly to the development of policies and interventions aimed at supporting the emotional well-being of young children in families affected by Baby blues. Keywords: Baby blues; Child Emotional Well-Being; Early Intervention; Mother-Child Interaction; Social Support